Du baromètre au piolet, cent cinquante ans de visions britanniques de la montagne - Michel Tailland (Anglophonia)
Throughout the XVIIIth and XIXth centuries, daring British travellers kept exploring and conquering mountain ranges up to then mostly "terra incognita Many of them, from William Brockedon, Edward Whymper, John Auldjo or Albert Smith not only wrote about them but also sketched or painted their landscapes thanks to their multi-faceted talents as writers, painters or engravers. This paper aims at analyzing the changes in the different points of view of a few generations of these artist/travellers who left an everlasting influence on contemporary visions of mountains. Far from the romantic or lyrical views of Shelley or Ruskin, their writings or etchings are therefore loaded with truth and emotion. They slowly changed the Rousseau-like view which had prevailed since the end of the XVIIIth century. Secondary literature, tales of vivid experiences, personal adventures or early mountain guidebooks, all of them embody the new and essential vision of an unknown world then becoming a craze to European elites